Indigenous continent : the epic contest for North America - Hämäläinen, Pekka, 1967- (Liveright Publishing Corporation, a division of W.W. Norton & Company, 2022)
"This nation's history and self-understanding have long depended on the notion of a "colonial America," an epoch that supposedly laid the foundation for the modern United States. In Indigenous Continent, Pekka Hämäläinen overturns the traditional, Eurocentric narrative, demonstrating that, far from being weak and helpless "victims" of European colonialism, Indigenous peoples controlled North America well into the 19th century. From the Iroquois and Pueblos to the Lakotas and Comanches, Native empires frequently decimated white newcomers in battle, forcing them to accept and even adopt Native ways. Even as the white population skyrocketed and colonists' land greed become ever more extravagant, Indigenous peoples flourished due to sophisticated diplomacy and flexible leadership structures. As Hämäläinen ultimately contends, instead of "colonial America" we should speak of an "Indigenous America" that was only slowly and unevenly becoming colonial. In our myth-busting era, this restoration of Native Americans to their rightful place at the very center of American history will be seen as one of the most important correctives yet"--